2010
DOI: 10.1099/mic.0.034249-0
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids of Gemmatimonas aurantiaca (Gemmatimonadetes): identification of a novel carotenoid, deoxyoscillol 2-rhamnoside, and proposed biosynthetic pathway of oscillol 2,2′-dirhamnoside

Abstract: Gemmatimonas aurantiaca strain T-27 T is an orange-coloured, Gram-negative, facultatively aerobic, polyphosphate-accumulating bacterium belonging to a recently proposed phylum, Gemmatimonadetes. We purified its pigments and identified them as carotenoids and their glycoside derivatives using spectral data. The major carotenoid was (2S,29S)-oscillol 2,29-di-(a-Lrhamnoside), and the minor carotenoids were (2S)-deoxyoscillol 2-(a-L-rhamnoside) and didemethylspirilloxanthin. Deoxyoscillol 2-rhamnoside is a novel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 25 publications
2
37
1
Order By: Relevance
“…In line with the presence of these carotenoids, we have identified six carotenogenesis genes in the AP64 genome (SI Appendix, Table S6) and propose a putative biosynthesis pathway for spirilloxanthin and oscillol series carotenoid biosynthesis (SI Appendix, Fig. S4), based on available genetic information and previously reported data (29,30).…”
Section: Proteobacteriasupporting
confidence: 60%
See 1 more Smart Citation
“…In line with the presence of these carotenoids, we have identified six carotenogenesis genes in the AP64 genome (SI Appendix, Table S6) and propose a putative biosynthesis pathway for spirilloxanthin and oscillol series carotenoid biosynthesis (SI Appendix, Fig. S4), based on available genetic information and previously reported data (29,30).…”
Section: Proteobacteriasupporting
confidence: 60%
“…In addition, AP64 contains several main carotenoids, mostly various derivatives of spirilloxanthin and oscillol (29) (Fig. 3C).…”
Section: Proteobacteriamentioning
confidence: 99%
“…Apart from the synthesis of a novel carotenoid by G. aurantiaca strain T-27 (31), not much has been reported regarding their physiology until recently, mainly due to the paucity of available isolates. The recent discovery of a full operon encoding type 2 photosynthetic reaction centers in the G. phototrophica strain AP-64 genome suggested that the Gemmatimonadetes phylum of bacteria may have adopted an oxygen-independent energy-generating metabolism to supplement an oxygen-dependent heterotrophic lifestyle in cases of transient hypoxia or anoxia (32).…”
Section: Discussionmentioning
confidence: 99%
“…S2). G. aurantiaca T-27 produced orange-colored carotenoids which are thought to act as a defense mechanism against oxygen radicals (Takaichi et al, 2010); it is hypothesized that the pink pigment produced by KBS708 may serve a similar function, contributing to KBS708 s oxygen tolerance. Microscopic imagery confirmed the presence of extracellular polymers causing cells to stick together (Fig.…”
mentioning
confidence: 99%